2022
DOI: 10.3389/fcell.2021.760912
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Differentially Expressed Profiles of mRNA N6-Methyladenosine in Colorectal Cancer

Abstract: Aim: To comprehensively profile the landscape of the mRNA N6-methyladenosine (m6A) modification in human colorectal cancer (CRC).Methods: Methylated RNA immunoprecipitation sequencing (MeRIP-seq) was explored to compare the difference in mRNA N6-methyladenosine (m6A) methylation between CRC tissues and adjacent normal control (NC) tissue. RNA-sequencing (RNA-seq) was performed to transcribe differentially expressed mRNAs. Conjoint analysis of MeRIP-seq and RNA-seq data was conducted to predict RNA-binding prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…B3GNT6 is a beta‐1,3‐N‐acetylglucosaminyl transferase that adds an N‐acetylglucosamine moiety to N‐acetylgalactosamine‐modified serine or threonine residues to affect biosynthesis and metabolism. Studies have found that B3GNT6 is closely related to a variety of disease processes, such as immunity deficiency, 21 colorectal cancer and m6A modification, 22 Together, these results indicate that B3GNT6 may be the downstream target of IGF2BP2. Survival analysis with TCGA data showed high B3GNT6 was related to lower survival status, and Spearman correlation analysis also showed the co‐expression of IGF2BP2 and B3GNT6 (Figure 5E ).…”
Section: Resultsmentioning
confidence: 99%
“…B3GNT6 is a beta‐1,3‐N‐acetylglucosaminyl transferase that adds an N‐acetylglucosamine moiety to N‐acetylgalactosamine‐modified serine or threonine residues to affect biosynthesis and metabolism. Studies have found that B3GNT6 is closely related to a variety of disease processes, such as immunity deficiency, 21 colorectal cancer and m6A modification, 22 Together, these results indicate that B3GNT6 may be the downstream target of IGF2BP2. Survival analysis with TCGA data showed high B3GNT6 was related to lower survival status, and Spearman correlation analysis also showed the co‐expression of IGF2BP2 and B3GNT6 (Figure 5E ).…”
Section: Resultsmentioning
confidence: 99%
“…RimK-like family member B (RIMKLB) is an enzyme that post-translationally modulates ribosomal protein S6 and contributes to the regulation of immune cell development [ 57 ]. RIMKLB has been identified as a prognostic biomarker in CRC [ 58 61 ]. Our results were consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, nine prognostic related genes were obtained to establish a risk model. Among the nine genes, ribosomal modification protein rimK like family member B (RIMKLB) is a protein-coding gene involved in the glutamine family amino acid metabolic process and cellular protein modification process, which is proved to be associated with prognosis and clinical stage ( Li et al, 2021 ). Asparaginase (ASPG) is known to be related to asparagine degradation.…”
Section: Discussionmentioning
confidence: 99%